(3eLehYI ahGFO aj GdYdhe GdfMhjIs
(3ChdgG (B:s
(3HSe Gddg GdCRdi GdUeO hMOg eLehY ahGFO hajg GdYdhe GdfMhjI ebJWa ef CaUM GdeDdaGJ ef gPG Gdaf hChVMgG hgj cJGH GHf Ybjd hGHf GdfGXe HGH GdcdGe GdeHfi Ef GdcdGe KdGKI CbSGe GSe haYd hMQa s
(3BNQgG (B:s
(3hjLhR ajg GdEOZGe HTQW fbd MQcI Chd GdeKdKjf Edi GdSGcf fMh SJQ jSJQ SJGQkG Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdfMhs